Cytokine profile, differential somatic cell count, and oxidative status of Italian Mediterranean buffalo milk affected by the temperature–humidity index - Ciliberti, Maria Giovanna; Santillo, Antonella; Caroprese, Mariangela; Albenzio, Marzia (Frontiers in Veterinary Science, 2024)
In the context of climate change, there has been an increased interest in improving management practices for animals genetically adapted to extreme environmental conditions, such as buffaloes. The temperature–humidity index (THI) is used to determine the severity of heat stress in livestock. This study aimed to evaluate the cytokine profile, oxidative staus, differential somatic cell count (DCC), and the surface expression and activity of myeloperoxidase (MPO) in the somatic cells (SCs) of buffalo. Milk samples (n = 216) were collected from the spring to summer season under three different THI classes (THI < 72; ≤72 THI < 76, and THI ≥ 76). The cytokine profile was determined using ELISA, and the expression of DSCC and MPO was determined by flow cytometry. MPO activity was performed on SC extracts using a specific ELISA kit. Oxidative status was determined by the antioxidant/oxidant balance combining the free radical scavenging activity levels, and reactive oxygen and nitrogenous species. The results on the cytokine profile showed that at the THI ≥ 76 the levels of both IL-10 and IFN-γ were highest. IL-1β secretion was lower at the THI < 72 than at the THI values ranging from ≤72 THI < 76. Higher levels of both TNF-α and IL-12 were registered in both THI < 72 and THI ≥ 76 classes. The level of IL-4 was higher in the THI ≥ 76 class than in the ≤72 to <76 range. Data on DCC showed a decrease in the percentage of macrophages and lymphocytes as the THI increased from the ≤72 to <76 range to THI ≥ 76. Furthermore, the highest percentage of polymorphonuclear leukocyte (PMNLs) was registered in both ≤72 to <76 and THI ≥ 76 classes. The MPO activity and surface expression on SC were lower at a THI above 76, which could be associated with an absence of inflammation. A condition of oxidative imbalance was registered as demonstrated by the lower levels of antioxidant/oxidant balance along with increasing THI. Present data demonstrated that buffaloes were able to modulate the alteration of immune response activated by heat stress throughout a series of cross-linked mechanisms involving cytokine networks, different somatic cell distribution, and oxidative status.